Finite Element Simulation of Welding Distortion in Dissimilar Joint by Inherent Deformation Method - Farajpour,Mehdi (2018)
Abstract Fusion welding is widely used to join different parts to each other in various industries. However, welding-induced distortions sometimes cause problems such as misalignment during assembling and impose costs for their removal. Thus, it is imperative to predict and mitigate these problems to improve weldment quality and also reduce fabrication costs. In this study, a dissimilar welded structure was first simulated with 3D solid and shell elements in ANSYS finite element software, and welding-induced deformations were then calculated. Afterwards, the constructed weldment was simulated using an inherent deformation method, and its results were compared with experimental measurements and 3D answers. This comparison showed that it was possible to simulate a dissimilar welded joint using an inherent deformation method in order to reduce the time and cost of modeling evenat the expense of a small error.